The Influence Of Leadership Style, Motivation, And Work Discipline On Employee Performance Pt. Putra Soegama Group - Nanda Khairul Asry (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
This research aims to analyze the potential influence of leadership style, motivation, and work discipline on employee performance. This research falls under the category of explanatory research, encompassing all employees in the research population. This research used non-probability sampling and judgmental sampling methods to select a sample of 100 workers. The researcher collected information through questionnaire distribution and analyzed the data using a quantitative descriptive approach. Research findings show that leadership style, motivation, and work discipline have a positive and significant impact on employee performance. Leadership style, with a regression coefficient of 0.371 and a t statistic of 4.450, confirms a significant positive influence on performance. Likewise with motivation, which has a regression coefficient of 0.176 and a t statistic of 2.025, and work discipline, which has a regression coefficient of 0.381 and a t statistic of 4.489, both of which also make a significant positive contribution to performance. Together or simultaneously, leadership style, motivation, and work discipline are able to explain as much as 70.7% of the variation in employee performance. Other variables or factors not included in this study account for the remaining 30.4%. These findings provide a comprehensive picture of the factors that influence employee performance, making a significant contribution to the understanding of the complex dynamics of the work environment.